Modern South Asia : history, culture, political economy - Bose, Sugata, 1956-; Jalal, Ayesha (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The fifth edition of Modern South Asia draws on the newest historical research and scholarship in the field to interpret and debate key developments in modern South Asian history and historical writing, covering the diverse spectrum of the subcontinent's social, economic and political past. Jointly authored by two leading Indian and Pakistani historians, this definitive study offers a rare depth of historical understanding of the politics, cultures and economies that have shaped the lives of more than a fifth of humanity. This new edition on the 75th anniversary of independence and partition brings the narrative up to the present day, discussing recent events and addressing new themes such as the capture of state power in India by the forces of religious majoritarianism, economic development in the context of the 'rise' of Asia and strategic shifts occasioned by the US withdrawal from Afghanistan and China's increasing role in the region. Providing fresh insights into the structure and ideology of the British raj, the meaning of subaltern resistance, the refashioning of social relations along lines of caste, class, religion and gender, the different strands of anti-colonial nationalism and the dynamics of decolonization, this is an essential resource for all students of the modern history of South Asia in an Indian Ocean and global context"--
South Asian history : an introduction -- Modernity and antiquity : interpretations of ancient India -- Pre-modern accommodation of difference : the making of Indo-Islamic cultures -- The Mughal Empire : state, economy, and society -- India between empires : decline or decentralization? -- The transition to colonialism : resistance and collaboration -- The first century of British rule, 1757 to 1857 : state and economy -- Company Raj and Indian society, 1757 to 1857 : reinvention and reform of tradition -- 1857 : rebellion, collaboration and the transition to Crown Raj -- High noon of colonialism, 1858 to 1914 : state and political economy -- A nation in making? : 'rational' reform, 'religious' revival, 1858 to c. 1900 -- A nation in making? : Swadeshi nationalism and internationalism, 1905-1918 -- Colonialism under siege : state and political economy after World War I -- Gandhian nationalism and mass politics in the 1920s -- The Depression decade : society, economics and politics -- Nationalism and colonialism during World War II and its aftermath : economic crisis and political confrontation -- The partition of India and the creation of Pakistan -- 1947 : memories and meanings -- Post-colonial South Asia : state and economy, society, and politics, 1947-1971 -- Post-colonial South Asia : state and economy, society, and politics, 1971 to c. 2000 -- South Asia in the twenty-first century -- Decolonizing South Asian history : a 75th anniversary perspective.
Includes bibliographical references and index.
GenEd
Book Finder International
Keywords: South Asia -- History